\(\dfrac{-2}{5}-\dfrac{3}{5}-\dfrac{2}{5}-\dfrac{3}{5}+\dfrac{4}{9}\)
a, \(\dfrac{1}{3}-\dfrac{1}{4}:\dfrac{2}{5}\)
b, \(\dfrac{6}{7}-\left(\dfrac{5}{6}+\dfrac{1}{3}\right)-\left(\dfrac{2}{3}+\dfrac{1}{7}\right)\)
c, \(\dfrac{-5}{9}.\dfrac{2}{5}+4\dfrac{5}{9}+\dfrac{5}{9}.\dfrac{-3}{5}\)
d, \(3\dfrac{1}{2}-\left(5\dfrac{4}{7}-1\dfrac{1}{2}\right):0,75\)
a) `1/3 - 1/4 : 2/5 = 1/3 - 5/8 = -7/24`
b) `6/7-(5/6+1/3)-(2/3+1/7) = 6/7-5/6-1/3-2/3-1/7`
`=(6/7-1/7)-(1/3+2/3)-5/6`
`=5/7-1-5/6`
`=-47/42`
c) `-5/9 . 2/5 + 4 5/9 + 5/9 . (-3/5)`
`= -5/9 . 2/5 + 4 + 5/9 + (-5/9) . 3/5`
`=-5/9 . (2/5 + 3/5-1) + 4`
`=-5/9 . 0 +4`
`=4`
d) 3 1/2 - (5 4/7 - 1 1/2) : 0,75`
`=7/2 - (39/7 - 3/2) : 3/4`
`= 7/2 - 57/14 : 3/4`
`=7/2 - 38/7`
`=-27/14`
\(\dfrac{3}{7}\) + 4 = ?
\(\dfrac{5}{9}\) x 3 = ?
\(\dfrac{7}{8}\) - \(\dfrac{2}{9}\)= ?
5 - \(\dfrac{3}{4}\)= ?
\(\dfrac{5}{7}\) : 6 = ?
\(\dfrac{5}{6}\) x \(\dfrac{2}{7}\)= ?
3 + \(\dfrac{3}{4}\)= ?
\(\dfrac{3}{5}x\dfrac{4}{8}\) = ?
5 : \(\dfrac{3}{8}\)= ?
Mong mn trả lời
\(\dfrac{3}{7}+\dfrac{4}{1}=\dfrac{3}{7}+\dfrac{28}{7}=\dfrac{31}{7}\)
\(\dfrac{5}{9}\times3=\dfrac{5}{9}\times\dfrac{3}{1}=\dfrac{15}{9}=\dfrac{5}{3}\)
\(\dfrac{7}{8}-\dfrac{2}{9}=\dfrac{63}{72}-\dfrac{16}{72}=\dfrac{47}{72}\)
\(\dfrac{5}{1}-\dfrac{3}{4}=\dfrac{20}{4}-\dfrac{3}{4}=\dfrac{17}{4}\)
\(\dfrac{5}{7}:\dfrac{6}{1}=\dfrac{5}{7}\times\dfrac{1}{6}=\dfrac{5}{42}\)
\(\dfrac{5}{6}\times\dfrac{2}{7}=\dfrac{5\times2}{6\times7}=\dfrac{10}{42}=\dfrac{5}{21}\)
\(\dfrac{3}{1}+\dfrac{3}{4}=\dfrac{12}{4}+\dfrac{3}{4}=\dfrac{15}{4}\)
\(\dfrac{3}{5}\times\dfrac{4}{8}=\dfrac{3}{5}\times\dfrac{1}{2}=\dfrac{3\times1}{5\times2}=\dfrac{3}{10}\)
\(\dfrac{5}{1}:\dfrac{3}{8}=\dfrac{5}{1}\times\dfrac{8}{3}=\dfrac{40}{3}\)
a) \(\dfrac{3}{7}+4=\dfrac{3}{7}+\dfrac{4}{1}=\dfrac{3}{7}+\dfrac{28}{7}=\dfrac{31}{7}\)
b) \(\dfrac{5}{9}\times3=\dfrac{5\times3}{9}=\dfrac{15}{9}=\dfrac{5}{3}\)
c) \(\dfrac{7}{8}-\dfrac{2}{9}=\dfrac{63}{72}-\dfrac{16}{72}=\dfrac{47}{72}\)
d) \(5-\dfrac{3}{4}=\dfrac{5}{1}-\dfrac{3}{4}=\dfrac{20}{4}-\dfrac{3}{4}=\dfrac{17}{4}\)
e) \(\dfrac{5}{7}:6=\dfrac{5}{7}:\dfrac{6}{1}=\dfrac{5}{7}\times\dfrac{1}{6}=\dfrac{5}{42}\)
f) \(\dfrac{5}{6}\times\dfrac{2}{7}=\dfrac{5\times2}{6\times7}=\dfrac{10}{42}=\dfrac{5}{21}\)
g) \(3+\dfrac{3}{4}=\dfrac{3}{1}+\dfrac{3}{4}=\dfrac{12}{4}+\dfrac{3}{4}=\dfrac{15}{4}\)
h) \(\dfrac{3}{5}\times\dfrac{4}{8}=\dfrac{3\times4}{5\times8}=\dfrac{12}{40}=\dfrac{3}{10}\)
i) \(5:\dfrac{3}{8}=\dfrac{5}{1}:\dfrac{3}{8}=\dfrac{5}{1}\times\dfrac{8}{3}=\dfrac{40}{3}\)
\(\dfrac{1}{3}+\dfrac{2}{3}=\)
\(\dfrac{4}{5}+\dfrac{5}{6}=\)
\(\dfrac{4}{5}-\dfrac{3}{5}=\)
\(\dfrac{9}{8}-\dfrac{4}{2}=\)
\(\dfrac{8}{5}x\dfrac{5}{8}=\)
\(\dfrac{6}{7}x\dfrac{4}{7}=\)
\(\dfrac{4}{5}:\dfrac{4}{5}=\)
\(\dfrac{5}{5}:\dfrac{5}{5}=\)
a,
\(\dfrac{1}{3}+\dfrac{2}{3}=\dfrac{3}{3}=1\)
\(\dfrac{4}{5}+\dfrac{5}{6}=\dfrac{24}{30}+\dfrac{25}{30}=\dfrac{49}{30}\)
\(\dfrac{4}{5}-\dfrac{3}{5}=\dfrac{1}{5}\)
\(\dfrac{8}{5}x\dfrac{5}{8}=\dfrac{1}{1}=1\)
\(\dfrac{6}{7}x\dfrac{4}{7}=\dfrac{24}{49}\)
\(\dfrac{4}{5}:\dfrac{4}{5}=\dfrac{4}{5}x\dfrac{5}{4}=\dfrac{1}{1}=1\)
\(\dfrac{5}{5}:\dfrac{5}{5}=\dfrac{5}{5}x\dfrac{5}{5}=\dfrac{1}{1}=1\)
1) \(\dfrac{1}{3}+\dfrac{2}{3}=\dfrac{1+2}{3}=\dfrac{3}{3}=1\)
2) \(\dfrac{4}{5}+\dfrac{5}{6}=\dfrac{24}{30}+\dfrac{25}{30}=\dfrac{24+25}{30}=\dfrac{49}{30}\)
3) \(\dfrac{4}{5}-\dfrac{3}{5}=\dfrac{4-3}{5}=\dfrac{1}{5}\)
4) \(\dfrac{9}{8}-\dfrac{4}{2}=\dfrac{9}{8}-2=\dfrac{9}{8}-\dfrac{16}{8}=-\dfrac{7}{8}\)
5) \(\dfrac{8}{5}\times\dfrac{5}{8}=\dfrac{8\times5}{5\times8}=\dfrac{40}{40}=1\)
6) \(\dfrac{6}{7}\times\dfrac{4}{7}=\dfrac{6\times4}{7}=\dfrac{24}{7}\)
7) \(\dfrac{4}{5}:\dfrac{4}{5}=\dfrac{4}{5}\times\dfrac{5}{4}=\dfrac{4\times5}{5\times4}=\dfrac{20}{20}=1\)
8) \(\dfrac{5}{5}:\dfrac{5}{5}=\dfrac{5}{5}\times\dfrac{5}{5}=\dfrac{5\times5}{5\times5}=\dfrac{25}{25}=1\)
a,\(\dfrac{7}{8}\)x\(\dfrac{2}{5}\)
b,\(\dfrac{9}{4}\)\(-\)\(\dfrac{5}{6}\)
c,\(\dfrac{4}{7}\)x\(\dfrac{2}{5}\)
d,\(\dfrac{3}{5}\)+2
e,4 \(-\) \(\dfrac{3}{5}\)
g,3x\(\dfrac{4}{9}\)
h,\(\dfrac{9}{5}\): 2
a. 7/8 x 2/5 =7/20
b.9/4-5/6=17/12
c.4/7x2/5=8/35
d.3/5+2=13/5
e. 4-3/5=17/5
g.3x4/9=4/3
h.9/5:2=9/10
a) \(\dfrac{14}{40}=\dfrac{7}{20}\)
b) \(\dfrac{27}{12}-\dfrac{10}{12}=\dfrac{17}{12}\)
c) \(\dfrac{8}{35}\)
d) \(\dfrac{3}{5}+\dfrac{10}{5}=\dfrac{13}{5}\)
e) \(\dfrac{20}{5}-\dfrac{3}{5}=\dfrac{17}{5}\)
g) \(\dfrac{12}{9}=\dfrac{4}{3}\)
h) \(\dfrac{9}{5}x\dfrac{1}{2}=\dfrac{9}{10}\)
`@LQuyen`
\(\dfrac{7}{8}\times\dfrac{2}{5}=\dfrac{14}{40}\)
\(\dfrac{9}{4}-\dfrac{5}{6}=\dfrac{54}{24}-\dfrac{20}{24}=\dfrac{34}{24}\)
\(\dfrac{4}{7}\times\dfrac{2}{5}=\dfrac{8}{35}\)
\(\dfrac{3}{5}+\dfrac{2}{1}=\dfrac{3}{5}+\dfrac{10}{5}=\dfrac{13}{5}\)
\(\dfrac{4}{1}-\dfrac{3}{5}=\dfrac{20}{5}-\dfrac{3}{5}=\dfrac{17}{5}\)
\(3\times\dfrac{4}{9}=\dfrac{12}{9}\)
\(\dfrac{9}{5}:2=\dfrac{9}{10}\)
a) \(\dfrac{2}{5}+\dfrac{4}{3}:\dfrac{-2}{3}\)
b) \(3\dfrac{4}{5}-\left(2\dfrac{1}{4}+1\dfrac{4}{5}\right)\)
c) \(\dfrac{-3}{5}.\dfrac{4}{7}+\dfrac{3}{7}.\dfrac{-3}{5}+\dfrac{3}{5}\)
d) 40% \(-1\dfrac{5}{7}:\dfrac{3}{7}+\left|\dfrac{-9}{5}\right|\)
\(a.\dfrac{2}{3}+\dfrac{4}{3}:\dfrac{-2}{3}=\dfrac{2}{3}+\left(-2\right)=\dfrac{-4}{3}\)
\(b.3\dfrac{4}{5}-\left(2\dfrac{1}{4}+1\dfrac{4}{5}\right)\\ =3\dfrac{4}{5}-2\dfrac{1}{4}-1\dfrac{4}{5}\\ =\left(3\dfrac{4}{5}-1\dfrac{4}{5}\right)-2\dfrac{1}{4}\\ =2-2\dfrac{1}{4}=\dfrac{1}{4}\)
\(c.\dfrac{-3}{5}.\dfrac{4}{7}+\dfrac{3}{7}.\dfrac{-3}{5}+\dfrac{3}{5}\\ =\dfrac{-3}{5}\left(\dfrac{4}{7}+\dfrac{3}{7}\right)+\dfrac{3}{5}\\ =\dfrac{-3}{5}+\dfrac{3}{5}=0\)
a) \(\dfrac{2}{5}+\dfrac{4}{3}:\dfrac{-2}{3}\)
\(=\dfrac{2}{5}+\dfrac{4}{3}.\dfrac{-3}{2}\)
\(=\dfrac{2}{5}+-2\)
\(=\dfrac{2}{5}+\dfrac{-10}{5}\)
\(=\dfrac{-8}{5}\)
a) \(\dfrac{2}{5}+\dfrac{4}{3}:\dfrac{-2}{3}=\dfrac{2}{5}+-2=\dfrac{-8}{5}\)
b) \(3\dfrac{4}{5}-\left(2\dfrac{1}{4}+1\dfrac{4}{5}\right)=\dfrac{19}{5}-\dfrac{9}{4}-\dfrac{9}{5}=\left(\dfrac{19}{5}-\dfrac{9}{5}\right)-\dfrac{9}{4}=2-\dfrac{9}{4}=\dfrac{-1}{4}\)
c) \(\dfrac{-3}{5}.\dfrac{4}{7}+\dfrac{3}{7}.\dfrac{-3}{5}+\dfrac{3}{5}\)
\(=\dfrac{-3}{5}.\left(\dfrac{4}{7}+\dfrac{3}{7}\right)+\dfrac{3}{5}\)
\(=\dfrac{-3}{5}.1+\dfrac{3}{5}\)
\(=\dfrac{-3}{5}+\dfrac{3}{5}\)
\(=0\)
d) \(40\%-1\dfrac{5}{7}:\dfrac{3}{7}+\left|\dfrac{-9}{5}\right|\)
\(=\dfrac{2}{5}-\dfrac{12}{7}:\dfrac{3}{7}+\dfrac{9}{5}\)
\(=\dfrac{2}{5}-4+\dfrac{9}{5}\)
\(=\dfrac{-9}{5}\)
\(\dfrac{1}{2}.\)\(\dfrac{3}{5}+\dfrac{4}{7}:\dfrac{4}{5}-\dfrac{1}{70}\)
\(\left(\dfrac{2}{3}+\dfrac{1}{5}-\dfrac{4}{9}\right):\left(\dfrac{1}{3}+\dfrac{2}{5}-\dfrac{6}{9}\right)\)
= 3/10 + 4/7 . 5/4 - 1/10
= 3/10 + 5/7 - 1/70
= 1.
\(\dfrac{3}{10}+\dfrac{4}{7}.\dfrac{5}{4}-\dfrac{1}{70}=\dfrac{3}{10}+\dfrac{5}{7}-\dfrac{1}{70}=\dfrac{21}{70}+\dfrac{50}{70}-\dfrac{10}{70}=\dfrac{70}{70}=1\)
1) \(=\dfrac{1}{2}.\dfrac{3}{5}+\dfrac{4}{7}.\dfrac{5}{4}-\dfrac{1}{70}\)
\(=\dfrac{3}{10}+\dfrac{5}{7}-\dfrac{1}{70}\)
\(=\dfrac{21}{70}+\dfrac{50}{70}-\dfrac{1}{70}\)
\(=1\)
2)
\(=\left(\dfrac{30}{45}+\dfrac{9}{45}-\dfrac{20}{45}\right):\left(\dfrac{15}{45}+\dfrac{18}{45}-\dfrac{30}{45}\right)\)
\(=\dfrac{19}{45}:\dfrac{1}{45}\)
\(=\dfrac{19}{45}.45\)
\(=19\)
\(\dfrac{2}{5}\) x \(\dfrac{3}{4}-\dfrac{1}{8}\) \(= \)
\(\dfrac{4}{3}+\dfrac{1}{3}-\dfrac{1}{5}=\)
\(\dfrac{9}{20}-\dfrac{3}{5}\) x \(\dfrac{1}{4}\)\(= \)
\(\dfrac{2}{8}+\dfrac{2}{3}:\dfrac{4}{5}\)\(=\)
\(\dfrac{2}{5}\times\dfrac{3}{4}-\dfrac{1}{8}=\dfrac{1}{5}\times\dfrac{3}{2}-\dfrac{1}{8}=\dfrac{3}{10}-\dfrac{1}{8}=\dfrac{24}{80}-\dfrac{10}{80}=\dfrac{14}{80}=\dfrac{7}{40}\\ \dfrac{4}{3}+\dfrac{1}{3}-\dfrac{1}{5}=\dfrac{5}{3}-\dfrac{1}{5}=\dfrac{25}{15}-\dfrac{3}{15}=\dfrac{22}{15}\\ \dfrac{9}{20}-\dfrac{3}{5}\times\dfrac{1}{4}=\dfrac{9}{20}-\dfrac{3}{20}=\dfrac{6}{20}=\dfrac{3}{10}\\ \dfrac{2}{8}+\dfrac{2}{3}:\dfrac{4}{5}=\dfrac{2}{8}+\dfrac{2}{3}\times\dfrac{5}{4}=\dfrac{2}{8}+\dfrac{1}{3}\times\dfrac{5}{2}=\dfrac{2}{8}+\dfrac{5}{6}=\dfrac{1}{4}+\dfrac{5}{6}=\dfrac{6}{24}+\dfrac{20}{24}=\dfrac{26}{24}=\dfrac{13}{12}\)
e)\(\dfrac{7}{10}\cdot\dfrac{-3}{5}+\dfrac{7}{10}\cdot\dfrac{-2}{5}-\dfrac{3}{10}\)
f)\(\dfrac{-3}{7}\cdot\dfrac{5}{9}+\dfrac{4}{9}\cdot\dfrac{-3}{7}+2\dfrac{3}{7}\)
g)
\(\dfrac{5}{9}\cdot\dfrac{10}{17}+\dfrac{5}{9}\cdot\dfrac{9}{17}-\dfrac{5}{9}\cdot\dfrac{2}{17}\)
Mn giúp em với ạ
\(e.\dfrac{7}{10}\cdot\dfrac{-3}{5}+\dfrac{7}{10}\cdot\dfrac{-2}{5}-\dfrac{3}{10}\)
\(=\dfrac{7}{10}\cdot\left[\left(\dfrac{-3}{5}\right)+\left(\dfrac{-2}{5}\right)\right]-\dfrac{3}{10}\)
\(=\dfrac{7}{10}\cdot1-\dfrac{3}{10}=\dfrac{4}{10}=\dfrac{2}{5}\)
\(f.\dfrac{-3}{7}\cdot\dfrac{5}{9}+\dfrac{4}{9}\cdot\dfrac{-3}{7}+2\dfrac{3}{7}\)
\(=\dfrac{-3}{7}\cdot\left(\dfrac{5}{9}+\dfrac{4}{9}\right)+\dfrac{17}{3}\)
\(=\dfrac{-3}{7}\cdot1+\dfrac{17}{3}=\dfrac{-9}{21}+\dfrac{119}{21}=\dfrac{110}{21}\)
\(g.\dfrac{5}{9}\cdot\dfrac{10}{17}+\dfrac{5}{9}\cdot\dfrac{9}{17}-\dfrac{5}{9}\cdot\dfrac{2}{17}\)
\(=\dfrac{5}{9}\cdot\left(\dfrac{10}{17}+\dfrac{9}{17}-\dfrac{2}{17}\right)\)
\(=\dfrac{5}{9}\cdot1=\dfrac{5}{9}\)
\(\dfrac{2}{3}.\dfrac{-5}{7}\)
\(\dfrac{-1}{3}.\dfrac{5}{9}\)
\(\dfrac{-2}{5}.\dfrac{10}{4}\)
\(\dfrac{-3}{7}.\dfrac{5}{15}\)
\(\dfrac{-7}{3}.\dfrac{9}{21}\)
a: =-10/21
b: =-5/27
c: =-20/20=-1
d: =-15/105=-1/7
e: =-63/63=-1
\(\dfrac{10}{21}\)
\(\dfrac{5}{27}\)
\(1\)
\(\dfrac{1}{7}\)
\(1\)
Giúp mình với
a,\(\dfrac{-8}{9}\)-(\(\dfrac{6}{5}\)-\(\dfrac{8}{9}\))
b, \(\dfrac{-4}{9}\)+\(\sqrt{\dfrac{9}{16}}\)-\(\dfrac{4}{5}\).\(\dfrac{-1^2}{2}\)+25%
c,\(\dfrac{2}{3}\)+(\(\dfrac{-3}{4}\)).\(\dfrac{4}{9}\)
d,16\(\dfrac{3}{4}\) - (-\(\dfrac{6}{5}\)) - 28\(\dfrac{3}{4}\):(-\(\dfrac{6}{5}\))
a: \(=\dfrac{-8}{9}-\dfrac{6}{5}+\dfrac{8}{9}=-\dfrac{6}{5}\)
c: \(=\dfrac{2}{3}-\dfrac{1}{3}=\dfrac{1}{3}\)